Brazilian Aphidoidea: I. Key to families, subfamilies and account of the Phylloxeridae - Costa, Claudio L.; Eastop, V. F.; Blackman, Roger L. (Pesquisa Agropecuaria Brasileira, 1993)
Keys are provided for the identification of the families and subfamilies of Aphidoidea occurring in Brazil. Host plant and geographical distribution data of Phylloxeridae are also provided. The keys are illustrated by 67 line drawings. The check list of aphids occurring in Brazil indicates the presumed origin of each species. The origin of the Brazilian fauna is discussed.
Keywords: Brazilian Aphids; identification Keys; host plants; check list of Genera and Species; distribution